War and Peace in Canaan: Connecting geography with political and military affairs in ancient Israel through a classroom game - Trimm, Charlie (Teaching theology and religion, 2018)
This essay provides a brief overview of an educational board game developed by the author for use in upper division Old Testament classes. The game, extending in stages across the semester, heightens student learning by requiring strategic thinking about various historical, political, and geographical relationships. Appendices and links to online material provide full details necessary to adapt the game in local classrooms.